2017
DOI: 10.1158/0008-5472.can-16-1979
|View full text |Cite
|
Sign up to set email alerts
|

HSPA5 Regulates Ferroptotic Cell Death in Cancer Cells

Abstract: Ferroptosis is a form of regulated cell death driven by oxidative injury promoting lipid peroxidation, although detailed molecular regulators are largely unknown. Here we show that heat shock 70kDa protein 5 (HSPA5) negatively regulates ferroptosis in human pancreatic ductal adenocarcinoma (PDAC) cells. Mechanistically, activating transcription factor 4 (ATF4) resulted in the induction of HSPA5, which in turn bound glutathione peroxidase 4 (GPX4) and protected against GPX4 protein degradation and subsequent li… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

11
330
1

Year Published

2017
2017
2022
2022

Publication Types

Select...
9

Relationship

3
6

Authors

Journals

citations
Cited by 419 publications
(342 citation statements)
references
References 45 publications
11
330
1
Order By: Relevance
“…This erastin‐induced ATF4 elevation was inhibited when miR‐214 was forced to overexpress in these cancer cells. HSP5A, an anti‐ferroptosis molecule that is downstream to ATF4 (Zhu et al, 2017), showed similar expression patterns as ATF4 (Figure 3b–d). However, miR‐214 overexpression elevated the suppression of Nrf‐2 exposed to erastin (Figure 3c,d).…”
Section: Resultsmentioning
confidence: 62%
See 1 more Smart Citation
“…This erastin‐induced ATF4 elevation was inhibited when miR‐214 was forced to overexpress in these cancer cells. HSP5A, an anti‐ferroptosis molecule that is downstream to ATF4 (Zhu et al, 2017), showed similar expression patterns as ATF4 (Figure 3b–d). However, miR‐214 overexpression elevated the suppression of Nrf‐2 exposed to erastin (Figure 3c,d).…”
Section: Resultsmentioning
confidence: 62%
“…In human pancreatic ductal adenocarcinoma cells, HSPA5 prevented the degradation of GPX4, an antioxidant enzyme known to inhibit lipid peroxidation (Yang et al, 2014), thereby inhibiting ferroptosis (Zhu et al, 2017). Erastin upregulated HSPA5 mRNA and protein expression in a dose‐dependent manner, and ATF4 was responsible for this HSPA5 elevation (Zhu et al, 2017). In addition to inducing ATF4 downregulation, miR‐214 suppressed HSPA5 expression in hepatoma cells in vitro.…”
Section: Discussionmentioning
confidence: 99%
“…cDNA from various cell samples was amplified using real-time quantitative PCR with specific primers (Table S2). The data were normalized to 18S RNA and the fold change was calculated via the 2 −ΔΔCt method (Song et al, 2018; Zhu et al, 2017). Relative concentrations of mRNA were expressed in arbitrary units based on the untreated group, which was assigned a value of 1.…”
Section: Star Methodsmentioning
confidence: 99%
“…As a key component of the unfolded protein response, HSPA5 promotes cell survival under conditions of endoplasmic reticulum stress-induced autophagy. A recent study demonstrated that upregulation of HSPA5 is a negative regulator of ferroptosis in pancreatic cancer cells [65]. Increased HSPA5 expression limits lipid peroxidation in ferroptosis by directly protecting against GPX4 degradation [65].…”
Section: Molecular Interactions Between Ferroptosis and Autophagymentioning
confidence: 99%